Epigastric pain of unknown origin, esophageal and gastric involvement: a Henoch-Schönlein Purpura case report - Li, Mengmeng; Huang, Chaoyuan; Xing, Hailun; Luo, Shijuan; Lin, Yiqun; Kuang, Yuxiang; Wang, Jing; Huang, Suiping; Ye, Zhenhao (Frontiers in Medicine, 2025)
Henoch-Schönlein Purpura (HSP) is an acute systemic vasculitis that primarily affects the skin, gastrointestinal tract, kidneys and joints. It predominantly occurs in children but can occur at any age. We report a case of 48-year-old male patient suffering from unexplained epigastric pain alternating between relapses and remissions. The patient’s initial clinical manifestation was atypical, starting with severe epigastric pain, without cutaneous purpura, and with normal rheumatologic and immunologic markers, making diagnosis difficult. The patient was eventually diagnosed with HSP. This case highlights the importance of considering this diagnosis in patients with unexplained abdominal pain and emphasize the role of endoscopy in diagnosing complex cases.